Pelatihan Ecoprint Memanfaatkan Daun dan Bunga Sebagai Bahan Penunjang Pembelajaran IPA di Sekolah Alam Kampung Wisata Isyo Hills Rhepang Muaif, Jayapura - Warikar, Evie L.; Ramandey, Euniche (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
This community service activity with the theme of ecoprint training was carried out with the aims to increase the knowledge, skills, and understanding of students and teachers at Sekolah Alam